The Eclectic Paradigm of International Production: A Restatement and Some Possible Extensions - Dunning, John H. (Journal of International Business Studies, 1988)
This article reviews some of the criticisms directed towards the eclectic paradigm of international production over the past decade, and restates its main tenets. The second part of the article considers a number of possible extensions of the paradigm and concludes by asserting that it remains “a robust general framework for explaining and analysing not only the economic rationale of economic production but many organisational and impact issues in relation to MNE activity as well.”